Reformulasi Kewenangan, Kelembagaan, dan Kepegawaian Penghubung Komisi Yudisial: Upaya Penguatan Pengawasan Perilaku Hakim di Daerah - Zaki Priambudi; Bima Rico Pambudi; Natasha Intania Sabila (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2022)
The Judicial Commission is a product of reform that supervises and monitors the judges’ behavior. With time, there has been additional discretionary authority to the Judicial Commission to form liaisoninstitution in the regions if deemed necessary. However, as it turns out, the Judicial Commission Liaison could not carry out his duties optimally as an extension of the Judicial Commission in supervising the judges’ behavior in the regions. Therefore, this article aims to analyze the urgency of reformulation of the Judicial Commission Liaison and how the idea of strengthening the Judicial Commission Liaison could increase the effectiveness of supervision of the judges’ behavior in the regions. This article uses the juridical-normative research method and finds several shortcomings in the Judicial Commission Liaison arrangement, such as the absence of executive authority, the view of being a sub-secretary institution, and inadequate personnels’ recruitment, development, and career systems. To follow up on this problem, this article formulates several efforts to strengthen the Judicial Commission Liaison by adding executive authority, transferring the responsibility of the Judicial Commission Liaison to the Judicial Commission Chair, and improving the personnels’ recruitment, development, and career system. The efforts could start with amendments to the 1945 Constitution of the Republic of Indonesia, revisions to the Judicial Commission Law, and insertion to government regulation on the Judicial Commission Liaison.AbstrakKomisi Yudisial merupakan produk reformasi yang berfungsi mengawasi dan memantau perilaku hakim. Seiring dengan berjalannya waktu, terdapat penambahan kewenangan diskresional kepada Komisi Yudisial untuk membentuk lembaga penghubung di daerah sesuai dengan kebutuhan. Namun, dalam perjalanannya, Penghubung Komisi Yudisial tidak dapat menjalankan tugasnya dengan optimal sebagai perpanjangan tangan Komisi Yudisial dalam melakukan pengawasan perilaku hakim di daerah. Oleh karena itu, artikel ini bertujuan untuk menganalisis apa urgensi reformulasi Penghubung Komisi Yudisial dan bagaimana gagasan penguatan Penghubung Komisi Yudisial dapat meningkatkan efektivitas pengawasan perilaku hakim di daerah. Dengan menggunakan metode penelitian yuridis-normatif, artikel ini menemukan bahwa terdapat beberapa kekurangan dalam pengaturan Penghubung Komisi Yudisial seperti tidak adanya kewenangan eksekutorial, kesan sebagai lembaga sub-kesekretariatan, serta sistem rekrutmen, pengembangan SDM, dan karier pegawai yang tidak tepat. Untuk menindaklanjuti permasalahan itu, artikel ini memformulasikan beberapa penguatan Penghubung Komisi Yudisial dengan menambahkan kewenangan eksekutorial, mengalihkan pertanggungjawaban Penghubung Komisi Yudisial kepada Ketua Komisi Yudisial, serta memperbaiki sistem rekrutmen, pengembangan SDM, dan karier pegawai. Penguatan tersebut dilakukan melalui amandemen UUD NRI 1945, revisi UU KY, dan pengaturan Penghubung KY melalui peraturan pemerintah.